Hardness, Cohesiveness, and Adhesiveness of Oral Moisturizers and Denture Adhesives: Selection Criteria for Denture Wearers - Keiko Fujimoto; Norikazu Minami; Takaharu Goto; Yuichi Ishida; Megumi Watanabe; Kan Nagao; Tetsuo Ichikawa (MDPI AG, 2016)
The mechanical properties of seven denture adhesives and eight oral moisturizers, all of which are commercially available, were evaluated using a texture proﬁle analysis. A new assessment chart is proposed for the selection criteria of denture adhesive and oral moisturizers using a radar chart with three axes: hardness, cohesiveness, and adhesiveness.